FlexTrail Printing as Direct Metallization with Low Silver Consumption for Silicon Heterojunction Solar Cells: Evaluation of Solar Cell and Module Performance. Issue 12 (20th October 2022) - Schube, Jörg; Jahn, Mike; Pingel, Sebastian; De Rose, Angela; Lorenz, Andreas; Keding, Roman; Clement, Florian
Abstract : FlexTrail printing has been invented and developed for (fine‐line) printing of various fluids, e.g., particle‐based metal‐containing fluids, etchants, and liquid‐phase pyrophoric media. Compared to other printing techniques, FlexTrail is highly independent of the fluids' viscosity. Using this printing approach, feature sizes of 10 μm and below are reached. This work utilizes FlexTrail as a direct metallization method for printing of silver‐nanoparticle‐based front electrodes on busbarless silicon heterojunction (SHJ) solar cells. Thereby, only (9.4 ± 0.9) mg of silver is consumed for printing of a busbarless front grid, which exhibits 80 contact fingers of 156 mm in length. This means a silver reduction of more than 60% compared to screen printing. Solar cells with M2+ wafer size and FlexTrail‐printed front grids reach conversion efficiencies of up to (22.87 ± 0.01)%, which is similar to screen‐printed reference cells. To further demonstrate the practicability of FlexTrail metallization beyond cell level, a FlexTrail‐printed SHJ cell is further processed into a 200 mm × 200 mm‐sized one‐cell module applying SmartWire Connection Technology for interconnection. This module exhibits a maximum power of (5.0 ± 0.1) W, underlining the great potential of FlexTrail printing for the metallization of high‐power SHJ devices with significant silver reduction. Abstract : Herein, FlexTrail printing is further developed for direct metallization of silicon heterojunction solar cells. Compared to screen printing, FlexTrail allows for a silver reduction of more than 60% without significant efficiency losses of busbarless cells, promising a great cost‐saving potential. Using multiwire interconnection, one‐cell modules with FlexTrail‐printed front contacts reach up to (5.0 ± 0.1) W.